The Viability of an Escherichia coli O157:H7 Strain in Guayanes Cheese Using Immunomagnetic Separation as a Tool for Recovery - Tomás Rojas; Ana Peñuela; Giliana Pernía; Mónica Perdomo; Marielsa Gil; Doris Reyes (Universidad del Zulia,Facultad de Medicina,Departamento de Enfermedades Infecciosas y Tropicales, 2009)
The viability of an Escherichia coli O157:H7 strain in cottage-industry Guayanes cheese was determined by evaluating several isolation protocols based on immunomagnetic separation (IMS). Cheese units (25 g) were inoculated with 25 and 250 cel/g of this pathogen and stored at 4°C. The pieces were analized at 0, 2, 6, 8 and 10 days post-inoculation through several IMS protocols including two enrichment broths: buffered peptone water without inhibitors (BPW-WI) and buffered peptone water with vancomicyn, cefixime and telurite (BPW-VCT) and two immunoseparation isolation agars: MacConkey-sorbitol agar (MSA) and MacConkey-sorbitol agar with cefixime and telurite (MSA-CT). Results demonstrated the viability of the pathogen for up to 10 days post-inoculation, and during this time, for some of the schemes applied on the IMS base, an increase in recovery percentages was achieved, indicating that the number of inoculated cells increased with time. In terms of the utility of IMS for recovering the pathogen, variations in the isolation percentages were observed in terms of the enrichment broth and the level of inoculated cells. The biggest recovery percentages were obtained in pieces inoculated with 250 cel/g, with ranges between 35 and 85% (days 0 and 10 respectively) in the best IMS scheme (BPW-WI/IMS/MSA), while, at levels of 25 cel/g, in the best case (BPW-WI/IMS/MSA), 15% was not surpassed during the first six days. The best performing enrichment broth was BPW-WI (p<0.05) and differences in the recovery percentages (p>0.05) were not observed in relation to the agars (MSA and MSA-CT) used for sowing the immunoseparator.